CURRENT STATE OF NON-PERFORMED ASSETS IN THE BANKING SECTOR OF THE REPUBLIC OF UZBEKISTAN (E Global Congress, 2024)
Improving the efficiency of commercial banks in Uzbekistan is related to their active participation in lending to the real sector of the economy. However, commercial banks of our country face a number of difficulties and problems in lending activities. Especially today, there is a tendency to increase problematic assets in the composition of commercial banks' assets. Especially, this situation shows high growth rates in commercial banks with a state share. In particular, the fact that the share of problematic loans in the credit portfolio of Xalq Bank in 2021 was 19.7 percent indicates that the quality of this commercial bank's assets is decreasing.